2015
DOI: 10.1002/mc.22257
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonoyl‐ethanolamide activates endoplasmic reticulum stress‐apoptosis in tumorigenic keratinocytes: Role of cyclooxygenase‐2 and novel J‐series prostamides

Abstract: Non-melanoma skin cancer and other epithelial tumors overexpress cyclooxygenase-2 (COX-2), differentiating them from normal cells. COX-2 metabolizes arachidonic acid to prostaglandins including, the J-series prostaglandins, which induce apoptosis by mechanisms including endoplasmic reticulum (ER) stress. Arachidonoyl-ethanolamide (AEA) is a cannabinoid that causes apoptosis in diverse tumor types. Previous studies from our group demonstrated that AEA was metabolized by COX-2 to J-series prostaglandins. Thus, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 58 publications
5
52
0
Order By: Relevance
“…3C). These results are consistent with other reports that COX-2 is expressed in the perinuclear space in granulocytes [22] and HaCaT cells [23]. …”
Section: Lupus Nephritis Elevates Cox-2 Expression In Podocytessupporting
confidence: 94%
“…3C). These results are consistent with other reports that COX-2 is expressed in the perinuclear space in granulocytes [22] and HaCaT cells [23]. …”
Section: Lupus Nephritis Elevates Cox-2 Expression In Podocytessupporting
confidence: 94%
“…In order to verify that the effect of AEA is not restricted to NMSC cells, additional studies were performed in the human colorectal cell line, HCA‐7. Our previous studies determined that the antitumor activity of AEA is dependent upon COX‐2 ; therefore, we verified that COX‐2 was overexpressed in HCA‐7 cells (Supplemental Figure S3B). To determine whether AEA induced cell death and apoptosis in HCA7 cells, cell viability and caspase 3/7 activity were measured.…”
Section: Resultssupporting
confidence: 69%
“…The endocannabinoid, AEA, is a potential therapeutic for NMSC. Our previous studies showed that AEA selectively induced ER stress‐mediated apoptosis in NMSC cells that overexpress COX‐2 . Specifically, we demonstrated that the cytotoxic effects of AEA were most likely produced by the novel prostaglandin, 15d‐PGJ 2 ‐EA, which was synthesized as a consequence of the metabolism of AEA by COX‐2.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Furthermore, immunofluorescence analysis revealed that COX-2 signals were stronger in the cytoplasm and perinuclear space of Cd-treated cells than in that of control cells (Figure 3f), which was consistent with other reports that COX-2 expressed in the perinuclear space in granulocytes 21 and HaCaT cells. 22 …”
Section: Resultsmentioning
confidence: 99%